Histone deacetylase inhibitors in cancer therapy. A review - Hraběta, Jan; Stiborová, Marie; Adam, Vojtěch; Kizek, René; Eckschlager, Tomáš (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2014)
BACKGROUND: Despite recent success toward discovery of more effective anticancer drugs, chemoresistance remains a major cause of treatment failure. There is emerging evidence that epigenetics plays a key role in the development of the resistance. Epigenetic regulators such as histone acetyltransferases (HATs) and histone deacetylases (HDACs) play an important role in gene expression. The latter are found to be commonly linked with many types of cancers and influence cancer development. Overall, histone acetylation is being investigated as a therapeutic target because of its importance in regulating gene expression. This review summarizes mechanisms of the anticancer effects of histone deacetylase (HDAC) inhibitors and the results of clinical studies. RESULTS: Different HDAC inhibitors induce cancer cell death by different mechanisms that include changes in gene expression and alteration of both histone and non-histone proteins. Enhanced histone acetylation in tumors results in modification of expression of genes involved in cell signaling. Inhibition of HDACs causes changed expression in 2-10 % of genes involved in important biological processes. The results of experiments and clinical studies demonstrate that combination of HDAC inhibitors with some anticancer drugs have synergistic or additive effects. CONCLUSIONS: Even though many biological effects of HDAC inhibitors have been found, most of the mechanisms of their action remain unclear. In addition, their use in combination with other drugs and the combination regime need to be investigated. The discovery of predictive factors is also necessary. Finally, a key question is whether the pan-HDAC inhibitors or the selective inhibitors will be more efficient for different types of cancers.
Keywords: Gene Expression Regulation, Neoplastic; apoptóza; regulace genové exprese u nádorů; signální transdukce; buněčná diferenciace; nádory; Cell Cycle Checkpoints; kontrolní body buněčného cyklu; Histone Deacetylase Inhibitors; lidé; Neoplasms; inhibitory histondeacetylas; Antineoplastic Combined Chemotherapy Protocols; Humans; Apoptosis; Cell Differentiation; protokoly protinádorové kombinované chemoterapie; Signal Transduction